THE USE OF COMPUTER SUPPORT OF SOLVING PROBLEMS OF PROBABILITY - FECHOVA, Erika (Trends in education, 2013)
Currently, the schools try to introduce and use modern information and communication tools in the teaching process. The paper deals with the possibility to use supporting software products in teaching numerical mathematics to solve problems in probability and numerical statistics.
Keywords: information and communication technologies; MATLAB; probability